Preparation method of waste tire rubber high-value recycled polypropylene composite material for automobiles
Through the grinding and blending process, waste tire rubber is combined with recycled polypropylene and glass fiber, and the dispersion and performance are improved using a specific additive system, solving the problems of high energy consumption, high cost and reduced performance of waste tire rubber in polypropylene composite materials, and achieving high value-added and sustainable composite preparation.
Patent Information
- Application Number
- CN202411986371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
When the prior art recycles and utilizes waste tire rubber in polypropylene composite materials, it faces problems such as high energy consumption, high cost, reduced physical performance and poor compatibility.
High value-added automotive polypropylene composite materials are prepared by grinding waste tire rubber into 40 to 300 mesh micropowder and blending with recovered polypropylene, glass fiber and specific additive systems. The additive system consists of waxes and organic salts, which help improve the dispersion and mechanical properties of the rubber.
The uniform dispersion of recycled rubber in polypropylene composite material is achieved, which improves the physical and mechanical properties of the material, while reducing production costs and promoting environmental sustainability.
Smart Images

Figure CN119752034A_ABST
Abstract
Description
Technical Field
[0001] This patent relates to the redevelopment and utilization of recycled rubber from waste tires in polypropylene composite materials, specifically, to a high value-added recycled polypropylene composite material of waste tire rubber for automobiles and its preparation method. Technical Background
[0002] Waste tires, also known as end-of-life tires (ELT), are highly durable, non-biodegradable and flammable. They easily release a large amount of toxic chemicals during landfill and incineration, which is a global problem that cannot be ignored. At present, the total annual production of waste tires in the world is about 1 billion tons. As a major tire producer in the world, China accounts for more than 30% of the global production of waste tires, with an annual production of about 120 million tons. Recycling waste tires to provide new economic end uses is an important and urgent issue.
[0003] So far, waste tires have been successfully converted into a variety of valuable products. The recycling process usually includes initial crushing, metal separation, low-temperature crushing, and the separated and reconstructed rubber has been re-applied to a variety of rubber products, such as asphalt, walking mats and floor pads. In addition, more and more "tire-derived products" are being continuously developed and improved. Thermoplastic olefins (TPO) are one of them. It has a multi-billion-dollar market and is widely used in many fields, including automobiles, construction, and electronic equipment.
[0004] Adding recycled tire rubber to TPO composites has the advantages of increasing economic added value, reducing costs and promoting sustainable development. The main challenges in achieving this application are: 1) energy consumption and cost control in the recycling process; 2) the physical properties of products containing recycled rubber are often compromised due to tire oxidation; 3) the compatibility of recycled rubber with the TPO matrix needs to be improved.
[0005] In order to alleviate the above problems, the common practice is to grind tire rubber into particles of small particle size. U.S. Patent No. 6,265,454B1 describes that only by using very fine size recycled rubber (90 mesh or less, U.S. standard) can reasonable performance be maintained in a rubber composite material composed partly of recycled tire rubber powder, mainly because small size particles are more compatible with the matrix. However, grinding tire rubber into a finer size requires a complicated process, which will increase costs to a certain extent.
[0006] Another method of maintaining good physical properties of recycled rubber composites is to improve the dispersibility of reground rubber in the matrix. For example, U.S. Patent No. 2001 / 0004649A1 proposes the introduction of lubricant-tall oil, which helps rubber to be better dispersed in the polypropylene matrix. Similarly, U.S. Patent No. 005397825A discloses a method of mixing waste rubber with liquid chemical plasticizers and adhesives such as rosin acid, fatty acid, ester, sterol and unsaponifiable matter to plasticize rubber particles and expand them to form polyethylene (PE) and polyethylene terephthalate (PET) homogeneous composite materials. However, these additives not only bring about odor problems, limit their application, but also bring cost pressure on finished materials. Summary of the invention
[0007] The present invention is a method for preparing a high value-added recycled polypropylene composite material of waste tire rubber for automobiles. A special formula system developed is disclosed, wherein the weight percentages of recycled polypropylene, tire rubber, filler, additive and masterbatch are 60-80wt%, 5-10wt%, 20wt%, 3-4wt% and 4wt% respectively. The recycled polypropylene used in the present invention is industrial recycled polypropylene crushed material, and its physical properties are shown in the following table:
[0008]
[0009] The purchased waste tire rubber was processed and ground into a powder with a size of 40 to 300 mesh (50 to 450 μm) in advance. Before the blending and extrusion granulation, the tire rubber powder was extruded to make a 50wt% PP-based masterbatch to improve the dispersion and processing performance of the rubber. The properties of the purchased rubber powder are shown in the following table:
[0010]
[0011] Adding 20%wt of glass fiber as filler can greatly improve the physical, mechanical and thermal properties of the material. The additive addition amount is 3-4%wt. The additive system consists of wax and nucleating agent. The wax is ethylene bis stearamide (EBS), an organic compound with the molecular formula (CH2NHC(O)C17H35)2 and the structure is shown below:
[0012]
[0013] It is a waxy white solid, commonly used as a lubricant, processing aid and release agent in polymers. The present invention extends its application to improving the dispersibility of rubber and demonstrates its good effect. The organic salt is a masterbatch of dicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, a masterbatch based on PP (20MFR), with a content of 5%wt. It is used as a nucleating agent together with fine talc (particle size 1-2μm), which helps to form a homogeneous composite material with high physical properties. Unlike previous reports, the addition of recycled rubber to TPO composite systems usually reduces the physical properties of the composite material due to its performance defects and limited dispersibility. The formulation system of the present invention can make the rubber well dispersed in the recycled polypropylene matrix, obtain high-performance, lower-cost recycled polypropylene composite materials, and promote environmental sustainability at the same time, which also paves the way for a wider range of high-end applications of recycled PP composites in automobiles.
[0014] The method for preparing the high value-added recycled polypropylene composite material from automobile waste tire rubber is characterized by the following steps:
[0015] (1) Preparation of rubber masterbatch: Rubber is crushed into fine powder to make masterbatch with 20-80%wt recycled rubber content. The main purpose is to evenly disperse the recycled rubber component in the finished material matrix;
[0016] (2) Use a special additive system consisting of lubricants and nucleating agents to maintain the mechanical properties of PP composites and solve the problem of using recycled rubber in thermoplastic olefin (TPO) systems;
[0017] (3) The raw materials are calculated by weight percentage: recycled polypropylene: 60-80 parts; tire rubber masterbatch: 5-10 parts; filler: 10-30 parts; additives: 2-6 parts; masterbatch: 2-5 parts;
[0018] (4) The masterbatch prepared from waste rubber extracted from waste tires is applied to automotive materials prepared from recycled polypropylene materials through blending modification.
[0019] In some embodiments of the present invention, the preparation method of the high value-added recycled polypropylene composite material of automobile waste tire rubber is as follows: the recycled polypropylene, tire rubber, filler, additive and masterbatch are put into a mixer according to corresponding proportions and mixed evenly, the mixture is added to the extruder hopper, the glass fiber side feed port is added to the extruder simultaneously, the extruder, cold water tank, pelletizer, air dryer, vibrating screen and other equipment are started, and the composite material is extruded, cooled and pelletized. The temperature distribution of the extruder from heating zones I to IX is 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw is 300rpm. The quenching water bath temperature is 25°C.
[0020] Before blending, the waste tire rubber is first processed and ground into a powder with a size of 40 to 300 meshes (50 to 400 μm), and then the tire rubber powder and polypropylene are extruded to make a PP-based masterbatch with a content of 20 to 80 wt% to improve the dispersion and processing performance of the rubber. The polypropylene resin is conventional polypropylene, and the melt flow rate of this polypropylene is 3 to 80 g / 10 min under the test conditions of 230° C. and 2.16 kg.
[0021] The lubricant in the special additive is selected from fatty acid amides, hydrocarbons, fatty acids, esters, alcohols, metal soaps, and composite lubricants with different chemical structures.
[0022] Part of the nucleating agent in the special additive is selected from one of fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates and wood acid and its derivatives, sodium benzoate and bis (p-tert-butylbenzoic acid) carboxyl aluminum, etc., and is made into PP matrix additive masterbatch with a content of 1 to 20 wt% based on polypropylene with a melt flow rate of 5 to 60 g / 10 min under the test conditions of 230°C and 2.16 kg. Another part of the nucleating agent is selected from talc powder with a particle size of 1 to 80 μm.
[0023] The sources of the recycled polypropylene (PP) resin in each component of the material raw material include but are not limited to the recycling of textiles, carpets, bottle caps, screwdriver handles and discarded automobile parts, and the melt flow rate of this polypropylene recycled material is 5 to 60 g / 10 min under the test conditions of 230° C. and 2.16 kg.
[0024] The filler in the material raw material is glass fiber, the fiber length is 2mm-10mm, the diameter is 2-8μm, and the surface of the glass fiber is covered with a coupling agent and a surface impregnating agent to obtain better interface bonding force.
[0025] The above process of applying the masterbatch prepared from waste rubber extracted from waste tires by blending and modification to the automotive material prepared from recycled polypropylene material is as follows:
[0026] First, the recycled polypropylene, tire rubber, filler, additives and masterbatch are put into a mixer in corresponding proportions and mixed evenly;
[0027] Secondly, the mixture is fed into the extruder hopper, and the glass fiber side feed port is simultaneously fed into the extruder;
[0028] Next, start the extruder, cold water tank, pelletizer, air dryer, vibrating screen and other equipment, and set the relevant parameters according to the process requirements of the production instruction sheet;
[0029] Finally, the molten material is continuously and stably transported to the machine head, and then enters the cold water tank to keep the material in a predetermined shape and solidify. The extruded and shaped material is then input into the pelletizer to cut the round strip plastic into pellets. After air drying and vibration screening, a polypropylene composite material containing recycled waste tire rubber for automotive parts is finally obtained.
[0030] In view of the above problems and current situation, the present invention starts from the development needs of the automobile industry and combines the polypropylene material modification and processing technology to provide a high-value-added recycled polypropylene composite material for automobile waste tire rubber and its preparation method, successfully applying the waste rubber particles extracted from waste tires to the modified polypropylene material for automobile interior and exterior decoration prepared from recycled polypropylene materials, effectively solving the dispersion problem of recycled rubber in the composite material matrix, and the mechanical performance loss caused by the addition of recycled rubber. Considering the cost, the material performance is maintained as much as possible. That is, while achieving the industry demands of low carbon and green circulation, it also realizes the high-value-added recycling of waste tire waste.
[0031] The key technical advantages in the formula of the present invention are summarized as follows:
[0032] (1) Crushing the rubber into fine powder to prepare a masterbatch with 50% recycled rubber content for uniform dispersion;
[0033] (2) The additive system consisting of wax and organic salt maintains the mechanical properties of the final PP composite material, solving the problem of using recycled rubber in TPO system;
[0034] (3) provided the first example of a high-performance RPP composite containing recycled tire rubber and demonstrated its application in automotive parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a photo of a product according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and outstanding advantages of the present invention clearer, the present invention will be described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples. The additional aspects and advantages of the present invention will be further reflected in the following analysis and explanation. It should be noted that the following description is only used to explain the present invention, but is not used to limit the present invention.
[0037] raw materials
[0038] PP recycled material, carpet recycled polypropylene, American Wellman
[0039] 50wt% recycled rubber masterbatch, customized, Lingshou County Tianlong Mineral Products Processing Plant
[0040] Glass fiber, 305H, Chongqing International Composite Materials Co., Ltd.
[0041] Additive EBS, Qingdao Cyberrun New Material Technology Co., Ltd.
[0042] Additive Bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, commercially available
[0043] Masterbatch, black masterbatch BK028, Shanghai Pulit Composite Materials Co., Ltd.
[0044] Material performance test methods
[0045] Density test standard: ISO 1183; unit: g / cm^3; immersion method
[0046] Ash test standard: ISO 3451-1, -4; Unit: %; Test condition: 600℃;
[0047] Tensile strength test standard: ISO 527; unit: MPa; test conditions: tensile speed 5mm / min Tensile elastic modulus test standard: ISO 527; unit: MPa; test conditions: tensile speed 1mm / min Bending strength test standard: ISO 178; unit: MPa; test conditions: 2mm / min, 64mm
[0048] Flexural modulus test standard: ISO 178; unit: MPa; test conditions: 2mm / min, 64mm Simple supported beam notched impact strength test standard: ISO 179; unit: KJ / m^2; test conditions: 23℃ Izod notched impact strength test standard: ISO178; unit: KJ / m^2; test conditions: 23℃ Heat deformation temperature test standard: ISO 75; unit: ℃; test conditions: 0.45MPa, 120℃ / h Flow direction shrinkage test standard: ISO 294-4 unit: % Test conditions: test after 48h Vertical flow direction shrinkage test standard: ISO 294-4 unit: % Test conditions: test after 48h
[0049] Example 1
[0050] 72.25 parts of PP recycled materials, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0051] Example 2
[0052] 67.25 parts of PP recycled materials, 5 parts of recycled rubber masterbatch, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0053] Example 3
[0054] 64.75 parts of PP recycled materials, 7.5 parts of recycled rubber masterbatch, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0055] Example 4
[0056] 62.25 parts of PP recycled materials, 10 parts of recycled rubber masterbatch, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0057] Example 5
[0058] 67.45 parts of PP recycled materials, 5 parts of recycled rubber masterbatch, 0.25 parts of EBS, 0.3 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0059] Example 6
[0060] 67.55 parts of PP recycled materials, 5 parts of recycled rubber masterbatch, 0.25 parts of EBS, 0.2 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0061] Example 7
[0062] 67.35 parts of PP recycled materials, 5 parts of recycled rubber masterbatch, 0.15 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0063] Example 8
[0064] 67.4 parts of PP recycled materials, 5 parts of recycled rubber masterbatch, 0.1 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0065] Comparative Example 1
[0066] 72.25 parts of PP recycled materials, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0067] Comparative Example 2
[0068] 67.25 parts of PP recycled materials, 5 parts of rubber masterbatch, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0069] Comparative Example 3
[0070] 69.75 parts of PP recycled materials, 2.5 parts of rubber powder, 0.25 parts of EBS, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0071] Comparative Example 4
[0072] 67.5 parts of PP recycled materials, 5 parts of rubber masterbatch, 0.4 parts of organic salt bicyclo[2.2.1]heptane-2,3-dicarboxylic acid disodium salt, 0.1 parts of fine talc, 4 parts of masterbatch, and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port, and 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0073] Comparative Example 5
[0074] 67.75 parts of PP recycled materials, 5 parts of rubber masterbatch, 0.25 parts of EBS, 4 parts of color masterbatch and 3 parts of other additives were mixed evenly and added to the twin-screw extruder from the main feed port. 20 parts of glass fiber were added from the side feed port. Standard specimens were prepared by extrusion granulation and injection molding. The temperature distribution of the extruder from heating zones I to IX was 200, 200, 200, 190, 190, 190, 190, 190, 190°C. The speed of the main screw was 300rpm. The quenching water bath temperature was 25°C.
[0075] Table 1 Comparative Example Formula
[0076]
[0077] Table 2 Performance of the embodiment
[0078]
[0079] Table 3 Comparative Example Formula
[0080] Material Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PP recycled material 72.25% 67.25% 69.75% 67.5% 67.75% Rubber Masterbatch 5% 5% 5% Micronized rubber powder 2.5% EBS 0.25% 0.25% 0.25% 0.25% Organic salt 0.4% 0.4% 0.4% 0.4% Fine Talc 0.1% 0.1% 0.1% 0.1% Fiberglass 20% 20% 20% 20% 20% Masterbatch 4% 4% 4% 4% 4% Other additives 3% 3% 3% 3% 3%
[0081] Table 4 Comparative Examples Performance
[0082]
[0083] Tables 1 to 4 show the material formulations and corresponding performance evaluation results prepared in Examples 1 to 8 and Comparative Examples 1 to 5, from which the following conclusions can be drawn:
[0084] (1) The performance of Examples 1 to 8 is shown in Table 2. Compared with Example 1 without adding rubber masterbatch, Examples 2-8 show mechanical properties equivalent to 5% to 10% of the rubber masterbatch filling amount, indicating that the formulation of the present invention can effectively utilize waste tire rubber without sacrificing the physical properties of the PP composite material. Unlike previous reports that recycled tire rubber usually lowers the performance level of the composite material due to poor dispersibility and performance defects caused by oxidation of the recycled rubber itself, the high value-added recycled polypropylene composite material of waste tire rubber obtained in the present invention has relatively high physical properties and can therefore be used in automotive parts.
[0085] The key to this breakthrough is that the recycled tire rubber part is evenly dispersed in the PP matrix. In order to further confirm the above results, the present invention designed the comparative examples shown in Table 3. As shown in Table 4, the tensile, bending and impact properties of comparative examples 2 and 3, which added recycled rubber in masterbatch state, were better than those of comparative example 3 which added rubber powder. Therefore, modifying the rubber form from powder to masterbatch is more conducive to dispersion and thus ensures the physical properties of the final composite material.
[0086] (2) The present invention innovatively designs an additive system consisting of EBS wax, organic salt and micro-talc. By comparing Comparative Examples 2 and 4, it is obvious that without the addition of EBS, the bending strength and impact strength are significantly reduced, so the addition of EBS wax helps to disperse the recycled rubber more evenly, mainly because the EBS lubricant can prevent the agglomeration of rubber powder to a certain extent. In addition, by comparing Examples 2 and 5, the organic salt and micro-talc act together as nucleating agents, which help to increase the crystallinity of the composite material, further ensure its mechanical properties, and improve the modulus.
[0087] Figure 1 The photo of the automobile gutter bracket made by using the automobile polypropylene composite material prepared by the present invention with the additive system composed of EBS wax, organic salt and micro talc and recycled tire rubber masterbatch. This patent discloses a strategy for using recycled tire rubber in high-performance polypropylene composite materials. Finally, the rubber particles extracted from waste tires were successfully applied to the polypropylene composite material for automobile interior and exterior modification. The illustration is an example of the application of this patent, but it is not the only application protected by this patent.
Claims
1. A method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber, characterized in that: The steps are: (1) Preparation of rubber masterbatch: Rubber is crushed into fine powder to make masterbatch with 20-80%wt recycled rubber content. The main purpose is to evenly disperse the recycled rubber component in the finished material matrix; (2) Use a special additive system consisting of lubricants and nucleating agents to maintain the mechanical properties of PP composites and solve the problem of using recycled rubber in thermoplastic olefin (TPO) systems; (3) The raw materials are calculated by weight percentage: recycled polypropylene: 60-80 parts; tire rubber masterbatch: 5-10 parts; filler: 10-30 parts; additives: 2-6 parts; masterbatch: 2-5 parts; (4) The masterbatch prepared from waste rubber extracted from waste tires is applied to automotive materials prepared from recycled polypropylene materials through blending modification.
2. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: Before blending, the waste tire rubber is first processed and ground into a powder with a size of 40 to 300 meshes (50 to 400 μm), and then the tire rubber powder and polypropylene are extruded to make a PP-based masterbatch with a content of 20 to 80 wt% to improve the dispersion and processing performance of the rubber. The polypropylene resin is conventional polypropylene, and the melt flow rate of this polypropylene is 3 to 80 g / 10 min under the test conditions of 230° C. and 2.16 kg.
3. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: The lubricant in the special additive is selected from fatty acid amides, hydrocarbons, fatty acids, esters, alcohols, metal soaps, and composite lubricants with different chemical structures.
4. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: Part of the nucleating agent in the special additive is selected from one of fatty carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates and wood acid and its derivatives, sodium benzoate and bis (p-tert-butylbenzoic acid) carboxyl aluminum, etc., and is made into PP matrix additive masterbatch with a content of 1 to 20 wt% based on polypropylene with a melt flow rate of 5 to 60 g / 10 min under the test conditions of 230°C and 2.16 kg. Another part of the nucleating agent is selected from talc powder with a particle size of 1 to 80 μm.
5. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: The sources of the recycled polypropylene (PP) resin in each component of the material raw material include but are not limited to the recycling of textiles, carpets, bottle caps, screwdriver handles and discarded automobile parts, and the melt flow rate of this polypropylene recycled material is 5 to 60 g / 10 min under the test conditions of 230° C. and 2.16 kg.
6. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: The filler in the material raw material is glass fiber, the fiber length is 2mm-10mm, the diameter is 2-8μm, and the surface of the glass fiber is covered with a coupling agent and a surface impregnating agent to obtain better interface bonding force.
7. The method for preparing a high value-added recycled polypropylene composite material of automobile waste tire rubber according to claim 1, characterized in that: The process of applying the masterbatch prepared from waste rubber extracted from waste tires through blending modification to the automotive material prepared from recycled polypropylene material is as follows: First, the recycled polypropylene, tire rubber, filler, additives and masterbatch are put into a mixer in corresponding proportions and mixed evenly; Secondly, the mixture is fed into the extruder hopper, and the glass fiber side feed port is simultaneously fed into the extruder; Next, start the extruder, cold water tank, pelletizer, air dryer, vibrating screen and other equipment, and set the relevant parameters according to the process requirements of the production instruction sheet; Finally, the molten material is continuously and stably transported to the machine head, and then enters the cold water tank to keep the material in a predetermined shape and solidify. The extruded and shaped material is then input into the pelletizer to cut the round strip plastic into pellets. After air drying and vibration screening, a polypropylene composite material containing recycled waste tire rubber for automotive parts is finally obtained.
Citation Information
Patent Citations
Rubber and plastic bonding
US20010004649A1
Rubber recycling process and product
US5397825A
Rubber compositions containing ground tire rubber
US6265454B1
Tire rubber powder modified recycled plastic and preparation method thereof
CN103183856A
Method for preparing recycled regenerated plastic for 3D printing
CN110698806A